Answer:
The increase was exponential
After three months his expense was: $133.1
Step-by-step explanation:
The increase was exponential, because if we call x the initial price, then after the first month the new price p is:
[tex]p = x (1 + \frac{10\%}{100\%})\\\\p=x(1+0.1)[/tex]
After the second month, the new price is 10% of the price of the previous month, that is:
[tex]p = [x (1 + 0.1)](1 + 0.1)\\\\p = x (1 + 0.1) ^ 2[/tex]
After month n, the price is:
[tex]p = x (1 + 0.1) ^ n[/tex]
Note that the equation has the form of an exponential growth function, where x is the initial price and n is the number of months elapsed.
In this case [tex]x = 100[/tex] and [tex]n = 3[/tex]. So:
[tex]p = 100 (1 + 0.1) ^ 3\\\\p=\$133.1[/tex]